1984
DOI: 10.1002/app.1984.070290325
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl‐containing polyesters and polyurethanes from dibenzyl L‐tartrate

Abstract: SynopsisWe have prepared polyesters from succinyl chloride, adipoyl chloride, and telephthaloyl chloride with dibenzyl L-tartrate, polyurethanes from hexamethylene diisocyanate, toluene 2,4-diisocyanate, and methylene-bis(4-phenyl isocyanate) with dibenzyl L-tartrate. The molecular weights of these polymers were generally low except for one of the polyurethanes. These polymers were reduced to give those having carboxyl side groups. Potency for inducing interferon was tested for one of the polymers. The result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…They synthesized a series of diols containing sulfonic [45][46][47][48][49][50][51][52] and phosphoric acid [53][54][55] and used them as chain extenders with PU prepolymers to get anionomers. Similarly, anionomers containing carboxylate groups were prepared and studied by various groups [56][57][58][59][60][61][62][63][64][65][66][67][68][69]. Ionic diols containing sodium sulfonate groups have been prepared by the reaction of various diols with maleic anhydride and subsequent addition of sodium bisulfite across the unsaturated site.…”
Section: Polyurethane Anionomersmentioning
confidence: 99%
“…They synthesized a series of diols containing sulfonic [45][46][47][48][49][50][51][52] and phosphoric acid [53][54][55] and used them as chain extenders with PU prepolymers to get anionomers. Similarly, anionomers containing carboxylate groups were prepared and studied by various groups [56][57][58][59][60][61][62][63][64][65][66][67][68][69]. Ionic diols containing sodium sulfonate groups have been prepared by the reaction of various diols with maleic anhydride and subsequent addition of sodium bisulfite across the unsaturated site.…”
Section: Polyurethane Anionomersmentioning
confidence: 99%
“…Since the investi-gations of tartaric acid-based polyamides by Ogata et al 39 in the 1970s, various classes of polymers containing tartaric acid have been reported. Kuramoto et al 40 synthesized polyesters or polyurethanes having pendant carboxyl groups by polycondensation of dibenzyl L-tartrate with dicarboxylic chlorides or diisocyanates, respectively. Muñ oz-Guerra et al [41][42][43] reported the synthesis of a series of stereoregular polyamides and poly(ester amide)s derived from tartaric acid, and their hydrolytic degradability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, growing attention has been paid to the synthesis of polyurethane ionomers. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Polyols bearing ionic or ionizable functions are particularly useful as reactive components for the synthesis of self emulsifying functionalized so polyurethane segments. 45,46 On the basis of triethanolamine, boric acid and polyoxyethyleneglycols, hyperbranched ethers of boric acid used as the basic compounds for the preparation of polyurethanes of ionomeric nature were obtained.…”
Section: Introductionmentioning
confidence: 99%